Antibiotic Sensitivity Pattern Of Streptococcus Against Commercially Available Drugs & Comparison With Extract Of Wild Punica Granatum - ARCHANA DEVI,; V. SINGH,; A.B. BHATT, (International Journal of Pharma and Bio Sciences, 2011)
Streptococcus is the leading cause of dental diseases worldwide and is considered to be the most cariogenic of all of the oral bacteria. The total 150 dental plaque sample were collected from Uttranchal dental college and hospital dehradun and different dental clinics of dehradun. Out of 320 isolates recovered prevalence of Streptococcus sp. was 50%. 10 antibiotics were used against the recovered isolates. 80% of the recovered isolates revealed the sensitive activity against amoxicillin (25 mcg), ampicillin (25 mcg), chloramphenicol (30 mcg), erythromycin (30 mcg), clindamycin (30 mcg), tetracycline (30 mcg), penicillin (100 mcg) and resistant activity against metronidazole (30 mcg), ciprofloxacin (25 mcg), and gentamycin (25 mcg). The antibacterial activity of Punica granatum against the recovered isolates was studied by using agar well diffusion method. Out of four different solvents used in the present study 90 % of the recovered isolates showed the maximum zone of inhibition against the methanolic extract of Punica granatum i.e. 25 mm.